Electromyographic analysis of transversus abdominis/internal oblique muscles during the execution of pelvic patterns of proprioceptive neuromuscular facilitation - Ferro, Josepha Karinne de Oliveira; Martins, José Vicente Pereira; Ribeiro, Bruna Rhayane da Cunha Melo; Manta, Thaís de Siqueira; Lemos, Andrea; Amorim, Keytte Camilla Souza de; Barboza, Paulo José Moté; Moura Filho, Alberto Galvão de; Oliveira, Daniella Araújo de (Avanços em Medicina, 2025)
Objective: To evaluate the electromyographic response of the transversus abdominis/internal oblique muscles (TrA/IO) during the execution of the four pelvic patterns of proprioceptive neuromuscular facilitation (PNF). Methods: Cross-sectional study. Were evaluated 21 women aged 18-38 years. The right TrA/IO complex, ipsilateral to the execution of a PNF combination of isotonics technique was monitored by surface electromyography. Three repetitions were performed with two-minute intervals between them in the four PNF pelvic patterns: anterior elevation, posterior depression, anterior depression, and posterior elevation. For the analysis of the electromyographic signal, a period of 500ms adjusted to the central value was extracted and the Root Mean Square amplitude was analyzed. Descriptive statistics and ANOVA test was used with a 95% confidence interval. Results: There was a higher TrA/IO activity in the concentric phase in the anterior elevation pattern (36.2 ± 32.3%) when compared to previous depression (19.5 μV ± 12.9), posterior elevation (16.1 μV ± 8.7), posterior depression 14.6μV ± 5.9). In addition, in the antero-elevation there is greater activation of the TrA/IO muscle complex when compared to the other patterns (p <0.01). Conclusion: The higher EMG response of the TrA/IO found in the anterior elevation pattern reveals its usefulness for clinical use.